1987
DOI: 10.1113/jphysiol.1987.sp016404
|View full text |Cite
|
Sign up to set email alerts
|

Triggered activity in atrial fibres of canine coronary sinus: role of extracellular potassium accumulation and depletion.

Abstract: 1. Bursts of triggered activity can be induced in atrial fibres of the canine coronary sinus exposed to catecholamines. During a triggered burst there is an initial acceleration of rate accompanied by depolarization of the maximum diastolic potential (m.d.p.) followed by slowing of the rate and termination accompanied by hyperpolarization. 2. We have used extracellular K+-sensitive micro-electrodes (potassium ISE) to monitor extracellular K+ concentration ([K+]o) during and following triggered activity, while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

1987
1987
1994
1994

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
0
3
1
Order By: Relevance
“…6B that under these conditions only an increase in ITI would have been seen and if there was a small, slow decrease in IT, it would have gone undetected. In contrast to the reports above Henning et al (1987) observed an apparent rate-dependent decrease in the afterdepolarization in the canine coronary sinus: the after-depolarization was reduced after a burst of triggered activity. It may be important that in their study afterdepolarizations were induced by catecholamines rather than by Na'-pump block, and the bursts were typically about 250 s in duration.…”
Section: Summary Of the Rate-dependent Changes In Electrical And Mechcontrasting
confidence: 99%
See 2 more Smart Citations
“…6B that under these conditions only an increase in ITI would have been seen and if there was a small, slow decrease in IT, it would have gone undetected. In contrast to the reports above Henning et al (1987) observed an apparent rate-dependent decrease in the afterdepolarization in the canine coronary sinus: the after-depolarization was reduced after a burst of triggered activity. It may be important that in their study afterdepolarizations were induced by catecholamines rather than by Na'-pump block, and the bursts were typically about 250 s in duration.…”
Section: Summary Of the Rate-dependent Changes In Electrical And Mechcontrasting
confidence: 99%
“…Similarly, Vassalle & Mugelli (1981) have shown that IT, is enhanced in the wake of a short train of voltage-clamp pulses. Different results were obtained by Henning, Kline, Siegal & Wit (1987) who studied after-…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, high [K], has been shown either to decrease I,, (Vassalle and Mugelli 1981) or not to modify it (Kass et al 19'78b). Similarly, in the presence of catecholamines, high [K], either decreases V, , (Coetzee and Opie 1988) or facilitates (Henning et al 1987) repetitive discharge due to Vo,.…”
Section: Mechanismsmentioning
confidence: 99%